The DNA Helicase Recql4 Is Required for Normal Osteoblast Expansion and Osteosarcoma Formation: e1005160 - Ng, Alvin JM; Walia, Mannu K; Smeets, Monique F; Mutsaers, Anthony J; Sims, Natalie A; Purton, Louise E; Walsh, Nicole C; Martin, T John; Walkley, Carl R (PLoS genetics, 2015)
RECQL4 mutations are associated with Rothmund Thomson Syndrome (RTS), RAPADILINO Syndrome and Baller-Gerold Syndrome. These patients display a range of benign skeletal abnormalities such as low bone mass. In addition, RTS patients have a highly increased incidence of osteosarcoma (OS). The role of RECQL4 in normal adult bone development and homeostasis is largely uncharacterized and how mutation of RECQL4 contributes to OS susceptibility is not known. We hypothesised that Recql4 was required for normal skeletal development and both benign and malignant osteoblast function, which we have tested in the mouse. Recql4 deletion in vivo at the osteoblastic progenitor stage of differentiation resulted in mice with shorter bones and reduced bone volume, assessed at 9 weeks of age. This was associated with an osteoblast intrinsic decrease in mineral apposition rate and bone formation rate in the Recql4-deficient cohorts. Deletion of Recql4 in mature osteoblasts/osteocytes in vivo, however, did not cause a detectable phenotype. Acute deletion of Recql4 in primary osteoblasts or shRNA knockdown in an osteoblastic cell line caused failed proliferation, accompanied by cell cycle arrest, induction of apoptosis and impaired differentiation. When cohorts of animals were aged long term, the loss of Recql4 alone was not sufficient to initiate OS. We then crossed the Recql4fl/fl allele to a fully penetrant OS model (Osx-Cre p53fl/fl). Unexpectedly, the Osx-Cre p53fl/flRecql4fl/fl (dKO) animals had a significantly increased OS-free survival compared to Osx-Cre p53fl/fl or Osx-Cre p53fl/flRecql4fl/+ (het) animals. The extended survival was explained when the Recql4 status in the tumors that arose was assessed, and in no case was there complete deletion of Recql4 in the dKO OS. These data provide a mechanism for the benign skeletal phenotypes of RECQL4 mutation syndromes. We propose that tumor suppression and osteosarcoma susceptibility are most likely a function of mutant, not null, alleles of RECQL4.